FEMINISM THOUGHT IN LOUISA MAY ACLOTT’S LITTLE WOMAN - Wara T. Gaspersz; Tini Mogea; Sarah Kamagi; Imelda S. Lolowang (SoCul: International Journal of Research in Social Cultural Issues, 2022)
This research aims at analyzing the thoughts of feminism through the struggle that women faced in the 19th century reflected through Josephine March in Alcott’s Little Women. In conducting this research, the qualitative method was used. This study can be classified as library research since the data were collected through reading the novel and reading some related books. The novel can be categorized as the primary source and the other sources as secondary sources. The data were analyzed based on the kinds of struggle and its impact and then the result was presented descriptively. In analyzing the data, the researcher used feminism approach. The result showed that the feminist struggle was shown in some aspects, like social relations, education, and job. The struggle brought a negative impact not only on women but also on societies. The struggle is caused by the negative treatment received by the women. Society taught that women are less important and should listen to what man says also woman can be happy with the support of man. The thought of freedom is so far away from her and other women in that era.